Countering Protection Rackets Using Legal and Social Approaches: An Agent-Based Test. (2nd December 2018) - Székely, Áron; Nardin, Luis G.; Andrighetto, Giulia
Abstract : Protection rackets cause economic and social damage across the world. States typically combat protection rackets using legal strategies that target the racketeers with legislation, strong sentencing, and increasing the presence and involvement of police officers. Nongovernmental organizations, conversely, focus on the rest of the population and counter protection rackets using a social approach. These organisations attempt to change the actions and social norms of community members with education, promotional campaigns, and discussions. We use an agent-based model, which draws on established theories of protection rackets and combines features of sociological and economic perspectives to modelling social interactions, to test the effects of legal and social approaches. We find that a legal approach is a necessary component of a policy approach, that social only approaches should not be used because they lead to large increases in violence, and that a combination of the two works best, although even this must be used carefully.